The Curriculum of Islamic Religious Education in the Whirlwind of Independent Education and Its Implementation on Learning - Abdul Halim; Helmun Jamil; Miswanto Miswanto; Ita Tryas Nur Rochbani (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
The curriculum is an important tool in the learning process that should provide guidance and direction for educational performance. Islamic religious education as an effort to internalize fundamental, social, and moral values, urgently needs an effective and efficient curriculum. This research is a Library Research with literature studies related to the Islamic religious education curriculum and Independent Learning. The data analysis technique used is content analysis by categorizing data so that it can be formulated based on the problem under study. The collected data is analyzed by analytical descriptive methods. The approach used is a qualitative approach where the data is in the form of narratives or sentences, and this data is processed systematically to produce conclusions. This research is also a type of historical-philosophical research. The results showed that, first, the Islamic Religious Education curriculum in the vortex of independent education became a challenge in itself, where the rapid development of science and technology, changes in education ministry regulations that hinted at independent education, and the demands of the industrial revolution 4.0. Second, the implementation of the Islamic Religious Education curriculum in Independent Learning education must be adjusted to include the values of science and technology, social values, culture, and the demands of the industrial revolution 4.0. especially after the Covid 19 pandemic which has changed the paradigm of Islamic religious education.